The Early Cambrian Mianyang-Changning Intracratonic Sag and Its Control on Petroleum Accumulation in the Sichuan Basin, China. (16th August 2017) - Liu, Shugen; Deng, Bin; Jansa, Luba; Zhong, Yong; Sun, Wei; Song, Jinmin; Wang, Guozhi; Wu, Juan; Li, Zhiwu; Tian, Yanhong
Abstract : The older and deeper hydrocarbon accumulations receive increasing attention across the world, providing more technical and commercial challenges to hydrocarbon exploration. We present a study of an asymmetrical, N-S striking intracratonic sag which developed across the Sichuan basin, south China, from Late Ediacaran to Early Cambrian times. The Mianyang-Changning intracratonic sag is ~50 km wide, with its steepest part in the basin center. In particular the eastern margin shows its greatest steepness. Five episodes in the evolutions of the sag can be recognized. It begins in the Late Ediacaran with an uplift and erosion correlated to Tongwan movement. Initial extension occurred during the Early Cambrian Maidiping period, when more strata of the Maidiping Formation were deposited across the sag. Subsequently, maximum extension occurred during the Early Cambrian Qiongzhusi period that resulted in 450–1700 m thick Maidiping-Canglangpu Formations being deposited in the sag. Then, the sag disappeared at the Longwangmiao period, as it was infilled by the sediments. The intracratonic sag has significant influence on the development of high-quality reservoirs in the Dengying and Longwangmiao Formations and source-rock of the Niutitang Formation. It thus indicates that a high probability for oil/gas accumulation exists along the intracratonic sag, across the central Sichuan basin.